Employee Job Satisfaction: A Case Study of a Company (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This study aimed to study the level of job satisfaction of employees of a company and compare the job satisfaction of employees. The sample group consisted of 56 employees of a company. Data were collected using a questionnaire. Data were analyzed using a computerized statistical program to find percentages, means, standard deviations, T-tests, and F-tests (One-way ANOVA). The statistical significance level was set at 0.05. The research results found that: 1. The results of the analysis of the overall job satisfaction of employees were at a high level. When considering each of the 6 aspects, the satisfaction in the aspect of job characteristics had the highest mean of 4.26, followed by the aspect of policy and management, relationship with colleagues and supervisors, job security, job advancement, and salary and benefits had the lowest mean of 3.79. 2. The results of the comparison of job satisfaction found that employees with different genders, ages, education levels, current positions, income, and length of employment had significantly different job satisfaction at the statistical significance level of 0.05